An Unusual Transudative Pleural Effusion Succeeded by Pulmonary and Brain Edema and Death - Sayyed Gholam Reza Mortazavimoghaddam; H. R. Riasi (Case Reports in Pulmonology)
Here we report a 22-year old woman with massive and bilateral transudative effusion succeeded by pulmonary edema and brain edema and death. Investigations for systemic disorders were negative. Exacerbation of dyspnea after intravenous fluid infusion was a main problem. As effusion was refractory to medical treatment, the patient was referred for surgical pleurodesis and bilateral surgical pleurodesis were done separately. Postsurgically, dyspnea exacerbation occurred after each common cold infection. Vertigo and high intracranial pressure were also a problem postsurgically. CSF pressure was 225 mm/H2O. Therapeutic lumbar puncture was done in two sequential weeks, and the patient was on acetazolamide 250 mg/trivise a day. Despite the medical treatment, progressive dyspnea, headache, and high intracranial pressure followed by death nine months after pleurodesis. As there is a gradient of pressure between pleura and CSF, after pleurodesis brain edema must be a consequence of inversing this gradient. In conclusion, when there are any abnormalities about fluid volume or pressure in any of these cavities, we have to study other cavities.